(untitled) (Biological Sciences - PJSIR, 1995)
BiogenicaminesandtheirmetabolitesinthebraintissueoftheAmericanCockroachhavebeenidentifiedandquan- tified bydifferent methodsofextraction andderivatisation.The molecularionof thesederivatives carried mostof the ion current under NICI conditions, with potential limitsof detection lowto the picogram level.